Sacral neuromodulation treatment for urinary voiding dysfunctions: Results of treatment with the largest single-center series in a tertiary referral center in Turkey - KÜTÜKOĞLU, MEHMET UMUT (My University, 2022)
Background/aim: Sacral neuromodulation (SNM) is a minimally invasive treatment that modulates spinal reflexes to regulate bladder, urinary sphincter, and pelvic floor and has successfully been used in the treatment of refractory voiding dysfunctions. The aim of this study was to present our experience with SNM in a tertiary referral center with the largest number of patients and review the safety and efficacy of the procedure. Materials and methods: A total of 42 patients with refractory lower urinary tract symptoms were included into the study. After an initial test period, patients who showed more than 50% improvement in their symptoms underwent the second stage of SNM. Twelve patients had overactive bladder (OAB), bladder pain syndrome/interstitial cystitis (BPS/IC) and 17 had urinary retention. The clinical success was examined during follow-up by voiding diary, urodynamics, and global response assessment. Results: Between February 2015 and December 2020, a total of 29 patients underwent stages I&II SNM procedures. The mean ages of patients in OAB/BPS group and retention group were 40 (37–57 years) and 35 (27–44 years), respectively. Mean follow-up time was at least 1 year. Overall, 58.5% success rate was observed in OAB, BPS/IC, and urinary retention groups. Global response assessment score in both groups increased significantly (p = 0.001). No statistically significant difference was found between success or failure rates when sex and age were variable parameters (p > 0.05). Conclusion: SNM appears to be an effective and safe treatment option in restoring voiding dysfunctions in patients with refractory idiopathic and neurogenic voiding dysfunctions. Our initial series revealed favorable results; however, further studies with larger series and longer follow-up are needed.
Keywords: Sacral neuromodulation; efficacy; voiding dysfunction; treatment